Equine platelet concentrate preparation and validation - Bozorgmanesh, Rana (J Vet Intern Med, 2019)
BACKGROUND: Development of equine platelet concentrate (PC) would aid management of cases requiring transfused platelets (PLTs), where adminstration of whole‐blood or platelet‐rich plasma (PRP) might be contraindicated. OBJECTIVES: To test and validate a method for production of an equine PRP‐PC product. ANIMALS: Six healthy Thoroughbred geldings from a research herd. METHODS: In this prospective experimental study, whole blood was collected and processed through multiple centrifugation steps to yield 120 mL of PC. The PC was stored at 22°C and gently and continuously agitated. Measurements of PLT count, pH, and concentrations of glucose, lactate, electrolytes, lactate dehydrogenase (LDH), and aspartate aminotransferase (AST), as well as partial pressures of oxygen and carbon dioxide were performed on days 0, 1, 2, 3, 5, and 7. Platelet aggregometry and bacterial culture were also performed. RESULTS: The PC always had a PLT count of ≥550 × 10(3) cells/μL. Aggregometry graph amplitude (P < .0001) and area under the curve (P < .05) significantly decreased over time. Sodium, chloride, lactate (P < .0001), and oxygen (P < .01) concentrations significantly increased over time. pH (P < .001), glucose and bicarbonate concentrations (P < .0001) significantly decreased over time. There was no significant difference in potassium concentration, PLT count, LDH and AST activities and no bacterial growth from culture. CONCLUSIONS AND CLINICAL IMPORTANCE: The described technique yielded a PC that meets the standards of the American Association of Blood Banks for human PC.